The role of cardiac troponin-I as a prognostic tool for mortality in patients hospitalized with COVID-19. (3rd October 2022) - Quintal, J; Candjondjo, A P; Coelho, R A; Piteira, A R; Simoes, J S; Pereira, R; Noivo, D; Reis, A; Inacio, A; Farinha, J M; Esteves, A F; Ferreira, J S; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) has been associated with significant morbidity and mortality, with cardiovascular involvement being usual. Elevations in cardiac Troponin-I level has proposed as an independent biomarker for mortality among patients with COVID-19. Aim: To evaluate the role of high sensivity Troponin-I (hs-TnI) level at hospital admission in predicting 30 day in-hospital mortality and 6-month mortality in patients hospitalized with a COVID-19 diagnosis. Methods: We performed a retrospective single-center cohort study including consecutive patients aged 18 years and older who were admitted for COVID-19, during a 1-year period (n=818). We excluded patients with acute coronary syndrome (n=23), patients with acute heart failure (n=42), and patients in which hs-TnI level was not dosed at admission (n=163). Patients were divided into two groups according to hs-TnI levels: hs-TnI <19.8 vs hs-TnI ≥19.8 pg/mL. Primary outcomes were 30-day in-hospital mortality and 6-months mortality. According to the data distribution, appropriate statistical tests were conducted to compare independent samples. Multivariable logistic regression was used to analyze mortality risk. Receiver operator characteristics (ROC) curve and area under the curve (AUC) were obtained to determine the discriminative power of hs-TnI as a predictor of mortality. (Figure 1). Results: This cohort included 590 patients. Mean age was 71 ≥±15 years and 52.4% were men. Overall, 209 patients (35.4%) had elevated hs-TnI levels and 381 patients had normal hs-TnI levels. Individuals in the hs-TnI ≥19.8 pg/mL group were older (80±11 vs 66±14 years, p<0.001) and presented higher prevalence of chronic heart failure (24.9% vs 7.1%, p<0.001), hypertension (77.0% vs 57.5%, p<0.001), atrial fibrillation/flutter (19.1% vs 5.5%, p<0.001), prior stroke (12.4% vs 5.2%, p=0.001) and ischemic heart disease (12.4% vs 3.7%, p<0.001). There was no difference in length of hospital stay between the groups (8.0 [IQR 9.6] in hs-TnI 19.8 pg/mL group vs 9.0 [IQR 8.0] normal hs-TnI group, p=0.669). Troponin-I was the only independent predictor of in-hospital mortality (OR 3.80, CI 95%: 2.44–5.93, p<0.001), see Table 1. The troponin levels had the highest area under the receiver operating characteristic curv (AUC) with an AUC of 0.705 (95% CI: 0.667–0.742, p<0.001) for association with the in-hospital mortality (figure 1). There was no difference in 6-months mortality between the two groups. Conclusion: Acute myocardial injury is common in patients hospitalized with COVID-19. In the present study a TnI level ≥19.8 pg/mL was predictor of 30 days in-hospital mortality, suggesting that raised levels of this biomarker is associated with adverse prognosis. This tool might be useful for COVID-19 patient risk stratification. Further studies are needed to provide robust data and reliable recommendations on this theme. Funding Acknowledgement: Type of funding sources: None.